Characterization and purification of protease extracted from guava (psidium guajava) peel / Normah Ismail and Mariyah Faizal - Ismail, Normah; Faizal, Mariyah (2016)
This study was carried out to extract, partially purify and characterise protease from guava peel. The extracted protease was purified using 60% ammonium sulfate precipitation method followed by gel filtration chromatography. The obtained proteases were analysed for protein concentration, proteolytic activity, total proteolytic activity, specific activity, percent recovery, purification fold, molecular weight distribution, optimum temperature and pH. Guava peel contains 7.10% protein. The optimum temperature and pH of the protease was achieved within the range of 40 to 60°C and pH 4 to 6, respectively, where maximum activity identified was 50°C and pH 5. Total activity decreased with the purification steps involving 60% ammonium sulfate precipitation and dialysis but subsequently increased after being subjected to gel filtration chromatography. This study suggested that further purification using gel filtration chromatography increases the proteolytic activity of guava peel protease.